PENERAPAN MODEL PEMBELAJARAN PETA KONSEP DAPAT MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV MI MUHAMMADIYAH SUNGAI SEGAJAH KECAMATAN KUBU - Yati Azlina Yati Azlina; Zulkifli Zulkifli '; Lazim N Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : Classroom action researchwas conducted because of the low sciencelearning outcomes of students with an average of 58.8 olehkurangnya causedstudent interest in learning and lack of problem solving abilities of students inlearning science. To improve the learning outcomes of the fourth grade scienceSegajah River MI Muhammadiyah Kubu district, the school year 2013/2014Concept maps applied learning models. This study was conducted from April toJune 2014 subjects were fourth graders totaling 17 people. Average studentlearning outcomes in daily test first cycle is 72.4 with a good category. While onthe second cycle of daily test students increased to 76.8 with either category. Forthe average teacher activity in the first cycle is 68.8 pertemua first with enoughcategories, at the second meeting increased to 75, while the second cycle to thefourth meeting of teachers has increased activity with both categories is 81.2, thefifth meeting of the 87, 5 with very good category. While the activities of studentsin the first cycle is 62.5 pertemua first with enough categories, at the secondmeeting increased to 68.8. While in the second cycle to the fourth meeting of thestudent activity increased to 75 with either category, the fifth meeting of the 81.2with either category. From this study it can be concluded that the application ofthe concept map learning model to improve learning outcomes IPA fourth gradestudents of Muhammadiyah River MI Segajah Kubu district.Keywords: Mind Mapping, IPA Learning Outcomes